The prevalence of anemia, iron, vitamin B12, and folic acid deficiencies in community dwelling elderly in Ankara, Turkey. Issue 2 (March 2015) - Yildirim, Tekin; Yalcin, Ahmet; Atmis, Volkan; Cengiz, Ozlem Karaarslan; Aras, Sevgi; Varlı, Murat; Atli, Teslime
Highlights Anemia is a major problem with important consequences on health of older people. Prevalence studies of anemia in Turkey are mostly restricted to older outpatients. We study anemia and nutritional deficiencies in Turkish community dwelling elderly. Prevalence of anemia is 7% and prevalence of nutritional deficiencies is high.